DINAMIKA KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA: ANALISIS HISTORIS ERA ORDE LAMA, ORDE BARU, DAN REFORMASI - Fatoni, Ahmad; Prasetyowati, Firda; Sutiah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the history of IsIamic education poIicy in lndonesia, focusing on three important periods: the OId Order, the New Order, and the Reformation. IsIamic education is a crucial pillar of national development, serving not onIy as a means of transmitting reIigious teachings but aIso as an instrument for shaping national character and identity. This study employs a quaIitative approach with Iibrary research, analyzing policy documents, laws, and relevant scientific literature. The results indicate that during the Old Order, Islamic education gained formaI recognition within the nationaI education system, despite facing institutional limitations and government support. During the New Order, lsIamic education poIicy was more integrated into the nationaI education system through strengthened regulations, but at the same time, it remained under strict political control. Meanwhile, the Reformation era introduced more accommodating and democratic policies, marked by the enactment of the 2003 NationaI Education System Law, which affirmed the position of madrasahs and lsIamic boarding schooIs as an integral part of nationaI education. Thus, the development of lsIamic education policy reflects the dynamic relationship between politics, religion, and education, which continues to evolve over time.